Near-field effects and energy transfer in hybrid metal-oxide nanostructures - Herr, Ulrich; Achinuq, Barat; Benel, Cahit; Papageorgiou, Giorgos; Goncalves, Manuel; Boneberg, Johannes; Leiderer, Paul; Ziemann, Paul; Marek, Peter; Hahn, Horst (Beilstein Journal of Nanotechnology, 2013)
One of the big challenges of the 21st century is the utilization of nanotechnology for energy technology. Nanoscale structures may provide novel functionality, which has been demonstrated most convincingly by successful applications such as dye-sensitized solar cells introduced by M. Grätzel. Applications in energy technology are based on the transfer and conversion of energy. Following the example of photosynthesis, this requires a combination of light harvesting, transfer of energy to a reaction center, and conversion to other forms of energy by charge separation and transfer. This may be achieved by utilizing hybrid nanostructures, which combine metallic and nonmetallic components. Metallic nanostructures can interact strongly with light. Plasmonic excitations of such structures can cause local enhancement of the electrical field, which has been utilized in spectroscopy for many years. On the other hand, the excited states in metallic structures decay over very short lifetimes. Longer lifetimes of excited states occur in nonmetallic nanostructures, which makes them attractive for further energy transfer before recombination or relaxation sets in. Therefore, the combination of metallic nanostructures with nonmetallic materials is of great interest. We report investigations of hybrid nanostructured model systems that consist of a combination of metallic nanoantennas (fabricated by nanosphere lithography, NSL) and oxide nanoparticles. The oxide particles were doped with rare-earth (RE) ions, which show a large shift between absorption and emission wavelengths, allowing us to investigate the energy-transfer processes in detail. The main focus is on TiO2 nanoparticles doped with Eu3+, since the material is interesting for applications such as the generation of hydrogen by photocatalytic splitting of water molecules. We use high-resolution techniques such as confocal fluorescence microscopy for the investigation of energy-transfer processes. The experiments are supported by simulations of the electromagnetic field enhancement in the vicinity of well-defined nanoantennas. The results show that the presence of the nanoparticle layer can modify the field enhancement significantly. In addition, we find that the fluorescent intensities observed in the experiments are affected by agglomeration of the nanoparticles. In order to further elucidate the possible influence of agglomeration and quenching effects in the vicinity of the nanoantennas, we have used a commercial organic pigment containing Eu, which exhibits an extremely narrow particle size distribution and no significant agglomeration. We demonstrate that quenching of the Eu fluorescence can be suppressed by covering the nanoantennas with a 10 nm thick SiOx layer.
Keywords: confocal microscopy; energy transfer; field enhancement; light harvesting; luminescence; nano-antennas; nanosphere lithography; nanostructures; plasmonics; simulation; TiO2 nanoparticles